Optimal design for shared backup path protected elastic optical networks under single-link failure - Shen, Gangxiang; Wei, Yue; Bose, Sanjay (Journal of optical communications and networking, 2014)
This paper considers the network protection technique of shared backup path protection (SBPP) in comparison with 1 + 1 path protection for elastic optical networks. We develop integer linear programming (ILP) models to minimize both the required spare capacity and the maximum number of link frequency slots (FSs) used. We consider transponder tunability that corresponds to the condition of whether or not the same set of FSs is required to be used for both the working and protection lightpaths. We also apply the bandwidth squeezed restoration technique to obtain the maximum restoration levels for the affected service flows, subject to a limited FS capacity on each fiber link. Our studies show that the proposed SBPP technique requires much lower spare capacity compared to the traditional 1 + 1 path protection approach. The flexibility of allowing the working and protection lightpaths to use different sets of FSs (i.e., with full transponder tunability) has the advantage of reducing both the number of FSs needed and the spare capacity redundancy required.